Prevalensi dan Tingkat Kelulushidupan Ikan Mas (Cyprinus carpio) yang Diuji Tantang dengan Protein Spora Utuh Myxobolus Koi Di Tambak [ Prevalence and The Survival Rate Of Gold Fish (Cyprinus carpio Linn) that Challenced Whole Protein Spore Myxobolus Koi in Pond] - Gunanti Mahasri; Nedi Nedi; Mufasirin Mufasirin (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract One of parasite disease that often outbreak is protozoan disease that caused by Myxobollus koi, that recaqniced Myxobolusis. Starting at 2009 this disease included in fish quarantine disease, because it can caused fish sick and dead. This disease can to be big problem in aquaculture, it can caused mortality 60-90%, with the prevalence reach 100%. In 1974 and 1978 the myxobolusis case happened in Indonesia and it caused mortality antil 100% in seed stadium. The aims of this Research are to detect the prevalence of the gold fish (Cyprinus carpio Linn) that infected by Myxobolus koi that challence by spora protein of Myxobolus koi in pond and want know abaout the survival rate of gold fish (Cyprinus carpio Linn) that challence by protein spora of Myxobolus koi in pond. This Research is field experiment that consist to 4 group, this are : KP1= Controle (No challence by protein spore and nor infected by Myxobolus koi) ; KP2 = challence by protein spore and infected by the dose 600 µl/l/one fish and infeted by Myxobolus koi dengan with dose 80 spore / liter, KP3 = No challence by Protein spore with dose 600 µl/l/one fish and was infected by Myxobolus koi with dose 80 spore / liter and KP4 = challence with Protein spore and not infcteted by Myxobolus koi. The result showed that the highest prevalence 74% found on gold fish that infected by Myxobolus koi and not dipping by whole protein spore before scatter in pond and in 60 days age. Whole Protein spore of Myxobolus koi can be decreased the prevalence of the gold fish (Cyprinus carpio Linn) infected by Myxobolus koi in pond 47,8% for 30 days age, 62,1% for 60 days and 69% for 90 days age in pond. The Whole Protein spore of Myxobolus koi also can increased the survival rate of gold fish (Cyprinus carpio Linn) in pond from 29% to 81%, it means that whole protein spore can increased in 179,3%.